Ancient and modern democracy Two concepts of liberty? - Nippel, Wilfried 1950- (Cambridge University Press, 2015)
"Ancient and Modern Democracy is a comprehensive account of Athenian democracy as a subject of criticism, admiration and scholarly debate for 2,500 years, covering the features of Athenian democracy, its importance for the English, American and French revolutions and for the debates on democracy and political liberty from the nineteenth century to the present. Discussions were always in the context of contemporary constitutional problems. Time and again they made a connection with a long-established tradition, involving both dialogue with ancient sources and with earlier phases of the reception of Antiquity. They refer either to a common cultural legacy or to specific national traditions; they often involve a mixture of political and scholarly arguments. This book elucidates the complexity of considering and constructing systems of popular self-rule"...